Sex Determination in Racing Pigeons (Columba livia) Molecularly Using Young Feather Samples - Adelia, Ersa Imelda; Srihanto, Eko Agus; Rustiati, Elly Lestari; Master, Jani; Firwantoni, Firwantoni; Anggy, Fransiska Panasea; Neli Pratiwi, Dian (Jurnal Agrosci, 2025)
The racing pigeon (Columba livia) has an aesthetic value and is in high demand. Pigeon is monomorphic, difficult to distinguish between male and female individuals, especially at the age of offspring. Knowing the sex of birds from an early age is necessary to prepare male bird individual as racing bird. Accurate determination of the sex of racing pigeons from an early age was carried out to have scientific confirmation of the molecular method of determining the sex in racing pigeon. Under Lampung Disease Investigation Center program, molecular methods of PCR techniques using primers 2550F and 2718R were applied to determine the sex of bird based on the presence of Z and W chromosomes from young feathers of racing pigeons. Sampling young feathers was done in individual breeders in Kota Metro and East Lampung. Molecular analysis was carried out at the Biotechnology Laboratory of the Lampung Disease Investigation Center, consisted of extraction, amplification, electrophoresis, and data analysis. Fifteen young feather samples showed five male individuals with electrophoresis visualization formed one band measuring 600 bp and ten female individuals showed two bands measuring 600 bp and 400 bp.